Antibacterial Activity of Aerial Parts Of Different Species of Ziziphus Genus - Singh, Sudhir Kumar; Midha, Anil (Asian Journal of Pharmaceutical Research and Development, 2017)
The leaves and stem powder alcoholic extracts of Ziziphus ziziphus and Ziziphus xyloporus were selected from Ziziphus genus are tested for their antibacterial potential against E. coli ATCC 8739, S. typhi ATCC 23564, S. aureus ATCC 29736, K. pneumoniae ATCC 10031, S. fecalis ATCC 8043, B. subtilis ATCC 6633,S. boydi ATCC 9207, P.mirabilis ATCC 2124, B. cereus, M. luteus ATCC 29736.The alcoholic extracts of Ziziphus xyloporus shown more anti-microbial activity than Ziziphus ziziphus.